1999
DOI: 10.1034/j.1399-3003.1999.13e42.x
|View full text |Cite
|
Sign up to set email alerts
|

Hunter′s syndrome and associated sleep apnoea cured by CPAP and surgery

Abstract: A 42‐yr‐old male with Hunter′s syndrome presented with severe obstructive sleep apnoea syndrome (OSAS) and daytime respiratory failure. Continuous positive airway pressure (CPAP) therapy was initially ineffective and produced acute respiratory distress. Extensive Hunter′s disease infiltration of the upper airway with a myxoma was confirmed. Following surgery to remove the myxoma at the level of the vocal cords, CPAP therapy was highly effective and well tolerated. This report demonstrates the necessity of eval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 17 publications
0
16
0
Order By: Relevance
“…Laryngeal myxomas have also been reported to occur with mucopolysaccharidosis II (MPS II) or Hunter's syndrome [10,13]. MPS II is a storage disorder due to a deficiency in iduronate sulphatase characterized by the intracellular and extracellular accumulation of glycosaminoglycan.…”
Section: Syndromic Associationsmentioning
confidence: 99%
“…Laryngeal myxomas have also been reported to occur with mucopolysaccharidosis II (MPS II) or Hunter's syndrome [10,13]. MPS II is a storage disorder due to a deficiency in iduronate sulphatase characterized by the intracellular and extracellular accumulation of glycosaminoglycan.…”
Section: Syndromic Associationsmentioning
confidence: 99%
“…A review of the literature revealed only ten previously reported cases (Table I) (3)(4)(5)(6)(7)(8)(9)(10)(11)(12). Mean patient age is 58.2 years (SD 13.5; range 36-77 years).…”
Section: Discussionmentioning
confidence: 99%
“…This required a high CPAP level, although in comparative terms it was below previously reported CPAP levels of up to 20 cm H 2 O (Ginzburg et al 1990). Orliaguet et al report an intolerance to CPAP pressures > 12 cm H 2 O with the occurrence of dyspnea in their patients (Orliaguet et al 1999). The cause was found to be a myxoma in the upper respiratory tract; therefore, surgical resection of the myxoma in the area of the vocal cords was carried out.…”
Section: Case Reportmentioning
confidence: 98%
“…With this therapy, the patient has been asymptomatic up to September 2011. (Leighton et al 2001;Orliaguet et al 1999;Shapiro et al 1985). In many patients, these changes occur in the first or second decade of life, in particular when the clinical progression of the disease is severe, so that respiratory deterioration is a common cause of death (Young and Harper 1983).…”
Section: Case Reportmentioning
confidence: 99%